Preliminary optimization of emergency core cooling system with accident-tolerant fuels. (July 2020) - Wu, Di; Gui, Minyang; Zhang, Ran; Zhang, Jing; Ye, Tianzhou; Yang, Hongfa; Peng, Jingyang; Wu, Yingwei; Wang, Chenglong; Su, G.H.
Highlights: The oxidation kinetics models of ATF claddings were incorporated into RELAP5. Safety analysis of PWR loaded with ATFs was carried out during LOCA. Optimization schemes of ECCS were proposed based on the performance of ATFs. Abstract: Based on the excellent performance of accident-tolerant fuels (ATFs), the optimization schemes for the safety system of Chinese advanced three-loop pressurized water reactor during loss of coolant accident (LOCA) were proposed and corresponding feasibility analysis was carried out in this study. The modified system analysis code was used to safety evaluation and four ATF systems were investigated. Several modifications were made to the rod geometries in partial ATF systems to make up the poor neutron economic performance of FeCrAl and MoMAX . The emergency core cooling system (ECCS) was optimized during LOCA with different break sizes. The results show that it is feasible for all ATF systems to cancel the high pressure safety injection (HPSI) or cancel both HPSI and low pressure safety injection (LPSI) but add an extra accumulator (ACC). Also the safety of reactors fueled with ATFs can be guaranteed with only 0.35 times the original flowrate of LPSI during large break LOCA (LB-LOCA). In the scheme of replacing the original ECCS with two extra ACCs during LB-LOCA, reactors loaded with partial ATFs are safe, while UO2 -Zr systems are in danger as a contrast. This work could provide reference for the design of reactor safety system in the future.